Self-Care Knowledge of Hypertension Prevention and Control Among Women in Contemporary Ghana. Issue 6 (2nd November 2017) - Asmah, Emmanuel Ekow; Orkoh, Emmanuel
ABSTRACT: Background : There has been a growing body of literature on hypertension in many countries, but nonavailability of data hampered empirical research on this issue in Ghana.Purpose : This article presents new and nationally representative household survey evidence on determinants and benefits of self-care knowledge of hypertension prevention and control among contemporary Ghanaian women.Methods : The logistics and double hurdle estimation approaches are employed together with univariate distributions (percentages and means) to analyze the socioeconomic correlates of the risk of hypertension and self-care knowledge among women aged 15–49 from the Ghana Demographic and Health Survey (GDHS) 2014 data.Results : The results show that knowledge of hypertension, education, and ethnicity significantly influence women's risk of being hypertensive. In addition, women's own level of education and that of their partners, ethnicity, age, and wealth are important determinants of their knowledge of hypertension.Discussion : The results indicate potentials for public education toward self-care to impact positively on the risk of hypertension.Translation to Health Education Practice : The Ministry of Health must collaborate with other civil society organizations and design policies aimed at educating hypertensive patients, their families, and people who are at high risk for hypertension giving due cognizance to access to information, ethnic and geographical diversity, attitudes, and practices.